1998
DOI: 10.1002/(sici)1521-3935(19981101)199:11<2609::aid-macp2609>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler on kinetics and energy of activation of phase separation in poly(methyl methacrylate)/poly(vinyl acetate) blend

Abstract: SUMMARY The effect of a filler on the rate and energy of activation of phase separation was studied for binary poly(methy1 methacrylate)/poly(vinyl acetate) blends (system with LCST) using light scattering. It was found that the rate of phase separation of the filled blends at close quench depth AT = T-T, is much lower as compared with the unfilled one at close quench depth. The activation energy for the filled blends is lower than that of unfilled blends. The drop of the rate of phase separation and of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effect of inorganic particles on the structure of multiphase polymers has been demonstrated in both experimental and theoretical studies [21][22][23][24]. Generally, fillers can support the initiation of phase separation [24][25][26] (e.g., by composition [25] fluctuations due to preferential wetting of one polymer phase on the filler surface [26]), and they also have a pinning effect during the subsequent separation because they increase the viscosity, blocking mass transfer [23,[27][28][29] in the system. Especially in the case of RIPS, separation can also be influenced by NF-induced effects on the crosslinking reaction kinetics [30].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of inorganic particles on the structure of multiphase polymers has been demonstrated in both experimental and theoretical studies [21][22][23][24]. Generally, fillers can support the initiation of phase separation [24][25][26] (e.g., by composition [25] fluctuations due to preferential wetting of one polymer phase on the filler surface [26]), and they also have a pinning effect during the subsequent separation because they increase the viscosity, blocking mass transfer [23,[27][28][29] in the system. Especially in the case of RIPS, separation can also be influenced by NF-induced effects on the crosslinking reaction kinetics [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was found that behaviour of multicomponent polymer systems can be significantly altered by using nanofillers. The presence of nanofillers in polymeric mixtures can affect the thermodynamics of its phase behaviour, the kinetics of phase separation, and also the morphology formed in the two-phase region [6][7][8][9][10][11][12][13][14]. Bousmina et al [15,16] found in PS/PVME blend that organoclay changed the mechanism of phase separation from spinodal decomposition to nucleation and growth and affected the final morphology obtained after phase segregation.…”
Section: Introductionmentioning
confidence: 99%